ضمانات ثبات قانون الاستثمار الجزائري المقررة للمستثمر الأجنبي - بن يطو, محمد (University of Eloued جامعة الوادي, 2020)
تبحث الدول عن إعطاء الضمانات الكافية للمستثمرين من أجل تشجيعهم على الاستثمار لديها ، و من بين هذه الضمانات الثبات التشريعي أي مبدأ الاحتفاظ بالحقوق المكتسبة في ظل القوانين السابقة وفق العقد المبرم بين الدولة و المستثمر ، و رغم أنه يعد تجميدا للقانون و انتقاص من سيادة الدولة في حقها بتعديل و إلغاء القوانين ، إلا أنه يعد بمثابة تشجيعا للاستثمار بعدم إدخال التعديلات على الحقوق المكتسبة أو إلغائها . رغم أن هناك من يرى في هذا الشرط خلق لقانون ميت لا يمكنه مسايرة التطورات الحاصلة ، و لقد راعت الجزائر من خلال قوانين الاستثمار و من خلال الاتفاقيات المبرمة عدم المساس بالحقوق المكتسبة للمستثمرين. Countries are looking to give enough guarantees to investors in order to encourage them to invest in them, and among these guarantees is legal stability, that is, the principle of preserving the rights acquired under previous laws according to the contract concluded between the state and the investor،Although it is a freezing of the law and a diminution of the state’s sovereignty in its right to amend and abolish laws, it is an encouragement for investment by not introducing amendments to or canceling the acquired rights.Although there are those who see this condition creating a dead law that cannot keep pace with the developments taking place, and Algeria has taken care, through investment laws and through the concluded agreements, not to prejudice the acquired rights of the investors.
مجلد11، عدد3
Keywords: المستثمر-الحق ; ق المكتسبة-تعديل القانون-الضمانات; Investor-acquired rights-amendment of the law-guarantees